Teachers' Understanding in Implementing Liveworksheets in Learning (E-LKPD) - Chodijah, Siti; Rosdiana, Rina; Fahira, Diva Aulia; Lestari, Linda Yunia (Jurnal Pengabdian Masyarakat Inovatif, 2025)
This community service aims to improve the digital competence of teachers at SMAN 1 Sukaraja in developing interactive student worksheets using the Liveworksheets platform. Electronic student worksheets (E-LKPD) are digital worksheets used for interactive discussions. Through E-LKPD, teachers will find it easier to check answers directly and reduce paper use. The method consists of training and the use of pretest-posttest instruments. A total of 19 teachers participated, with 15 Likert-scale indicators used to assess their understanding before and after the training. The results showed an increase in the average score from 4.48 in the pretest to 4.88 in the posttest. This indicates a significant improvement in teachers’ understanding of Liveworksheets for E-LKPD development. It is recommended to conduct follow-up training integrating the platform into broader learning systems.